Effect of intrinsic nanoparticle pigmentation on the color stability of denture base acrylic resins - Goiato, Marcelo Coelho; Zuccolotti, Bruna Carolina Rossatti; dos Santos, Daniela Micheline; Sinhoreti, Mário Alexandre Coelho; Moreno, Amália (Elsevier, 2013)
Statement of problem: Intrinsic pigmentation is widely used to improve the esthetic features of denture base acrylic resins. However, acrylic resin may discolor over time. Purpose: The purpose of this study was to investigate the effect of intrinsic nanoparticle pigmentation on the color stability of acrylic resins. Material and methods: The acrylic resins, Onda Cryl, QC 20, Classico, and Lucitone, were evaluated. Twenty-one disk-shaped specimens (3 × 30 mm) were fabricated from each acrylic resin. Seven were colored with 3% Poli-Cor intrinsic pigment used to color denture base, 7 were colored with 7% pigment, and 7 were not pigmented. In addition, 7 specimens were fabricated containing only pigment. The specimens were thermally cycled 2000 times between 5°C and 55°C with a 30-second dwell time at each temperature. The specimen colors were measured with a spectrophotometer and evaluated with the CIE L*a*b* system before (B) and after thermal cycling (T). The pigment morphology was analyzed by using a scanning electron microscope (SEM) and energy-dispersive x-ray spectroscopy (EDS) techniques. The results were analyzed with 2-way nested ANOVA and Tukey HSD tests (α=.05). Results: Classico acrylic resin with and without pigment underwent the least color change, followed in order by Lucitone, Onda Cryl, and QC-20. The presence of pigments reduced the color change of the acrylic resins significantly (P<.05) for the specimens containing 7% pigment (0.32 ±0.18 ΔE). Titanium was the sole metallic component present in the pigment, probably in the oxide form (TiO2). Conclusions: Nanoparticle pigments enhanced the color stability of denture base acrylic resins.